Personality traits affect older adults' memory differently depending on the environmental support provided at encoding. (June 2022) - Taconnat, Laurence; Pinard, Florent; Vanneste, Sandrine; Bouazzaoui, Badiâa; Fay, Séverine; Martinez, Léa; Alibran, Emilie; Geraci, Lisa
Abstract: Research suggests that personality traits are associated with memory performance, particularly as people age. In two studies, we examined two personality traits (openness to experience and neuroticism) that have been hypothesized to modulate episodic memory performance in older adults. We tested the hypothesis that these traits would be differently associated with episodic memory according to the amount of cognitive support provided at encoding. We examined the role of these personality traits in free recall when performance was supported by prior task success versus no prior task success (Experiment 1) and by generating versus reading (Experiment 2). Results showed that prior task success and generating items led to superior memory performance. In both studies, openness to experience was positively associated with memory performance and neuroticism was negatively associated with memory performance. Further, openness accounted for the most variability in recall performance under conditions providing low cognitive support and neuroticism, on the other hand, accounted for recall in both high and low support conditions. Results suggest that neuroticism is a key personality trait implicated in memory performance, but for the most difficult memory tasks, a high level in openness may aid memory performance. Highlights: Environmental support increases memory performance in older adults. Previous task success increases memory performance in older adults. Word generation increases memory performance in older adults. Neuroticism is negatively related to memory regardless of environmental support. Openness is positively related to memory when the task is highly resource dependent.